A Host Factor GPNMB Restricts Porcine Circovirus Type 2 (PCV2) Replication and Interacts With PCV2 ORF5 Protein - Guo, Kangkang; Xu, Lei; Wu, Mengmeng; Hou, Yufeng; Jiang, Yanfen; Lv, Jiangman; Xu, Panpan; Fan, Zhixin; Zhang, Ruiqi; Xing, Fushan; Zhang, Yanming (Frontiers in Microbiology, 2019)
Porcine circovirus type 2 (PCV2) is the infectious agent of postweaning multisystemic wasting syndrome (PMWS). The recently discovered open reading frame 5 (ORF5) in PCV2 genome encodes a non-structural protein. Previous study revealed that ORF5 protein inhibits cell proliferation and may interact with host transmembrane glycoprotein NMB (GPNMB). However, whether the GPNMB affects PCV2 replication and the underlying molecular mechanisms are still unknown. In this study, the transcriptome maps of PCV2-infected and ORF5-transfected porcine alveolar macrophages 3D4/2 (PAM) cells were profiled. The GPNMB gene was down-regulated in PCV2-infected and ORF5-transfected PAMs. By using glutathione S-transferase (GST) pull-down, co-immunoprecipitation (co-IP) and confocal microscopy approaches, we convincingly showed that PCV2 ORF5 protein interacts with GPNMB. Furthermore, by utilizing lentivirus mediated overexpression or knockdown approach, we showed that the cellular GPNMB significantly inhibits PCV2 replication and ORF5 expression. Moreover, GPNMB overexpressing leads to an increased Cyclin A expression and a reduced S phase, whereas GPNMB knockdown causes a decreased Cyclin A expression and a prolonged S phase. In conclusion, we identified a novel host factor GPNMB that interacts with PCV2 ORF5 protein and restricts PCV2 replication.